History, tales, and sketches - Irving, Washington, 1783-1859. (New York, N.Y. : Literary Classics of the United States : Distributed to the United States by Penguin Putnam and to Canada by Penguin Books Canada, Ltd., 1983)
Contains Letters of Jonathan Oldstyle, Gent., and Salmagundi; Irving's satires and burlesques of early 19th- century New York; The Sketch book of Geoffrey Crayon, Gent.; and the original 1809 edition of his irreverent and hilarious A history of New York.
Letters of Jonathan Oldstyle, Gent. -- Salmagundi -- A history of New York -- The sketch book of Geoffrey Crayon, Gent.
Keywords: Social life and customs -- 19th century -- Fiction; Fantasy fiction, American; Hudson River Valley (N.Y. and N.J.) -- Fiction; Catskil Mountain region -- Fiction